Penerapan Model Berbasis Masalah Dalam Meningkatkan Kemampuan Belajar Siswa Kelas VII-A SMP Negeri 1 Sukabumi - Andini, Sri (FKIP Universitas Muhammadiyah Sukabumi, 2019)
This study aims to improve students' learning abilities and student responses to mathematics learning by applying problem-based learning models. This research was carried out using Classroom Action Research techniques carried out following the stages of Classroom Action Research proposed by Kemmis and MC Taggart, with the components of action being planning, implementing actions, observation, and reflection. This research was conducted in class VII-A of SMP Negeri 1 Sukabumi which was conducted in July to September 2016. The subjects of the study were students of class VII-A of SMP Negeri 1 Sukabumi, amounting to 39 students. The results of the study were before the implementation of student learning outcomes towards the concept and presentation of the new set reached a mastery level of 56%. In the implementation of the first cycle the application of the Problem-Based learning model of students was 67%, the second cycle of ability and student learning outcomes was 82%, while in the third cycle the action could reach 100%. After the implementation of the action there is an increase in students' understanding and learning outcomes of the material Concept and Presentation of the Set.